CURRENT STATE OF SOLAR PHOTOVOLTAIC PANELS WASTE MANAGEMENT OPERATIONS IN UKRAINE - KATENIN, Vadym; SAMOILENKO, Nataliia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper analyzes the steady trend of solar energy development, which is accompanied by the formation and accumulation of solar panel waste. This process requires the application of accomplished waste management and the development of waste disposal technologies. It was determined that the problem of waste solar photovoltaic panels becomes more urgent due to the military actions taking place on the territory of Ukraine. The general characteristics of waste for different types of panels are given. The heterogeneity of the materials of photovoltaic panels leads to an ambiguous classification and involves a combination of safe and dangerous components. It has been determined that photovoltaic panel waste can be divided into two hazard classes: hazardous waste and non-hazardous waste. The key points of solar panel waste management operations are characterized in accordance with the Law of Ukraine "On Waste Management" and EU Legislation. The main points of disposal of unusable photovoltaic panels with recovery of valuable raw materials are described. It is noted that there are significant differences in the material composition of crystalline silicon panels and thin film modules. It is noted that two processing types of PV modules are currently distinguished - coarse and fine, and the most effective steps in the preparatory stage of disposal are also determined. In general, PV panel waste disposal operations combine mechanical and chemical material extraction processes. The imperfection of the legislative and regulatory framework in the field of waste management, the increase in the ecological danger of the generation and accumulation of waste, the imperfection of the information base and waste monitoring, the insufficient development of the processes of organizing the processes of collection, accumulation and transfer of waste for disposal, the insufficiency of proposals for methods of processing and disposal of solar panels waste as a valuable resource of secondary raw materials are notable as the main problems in the field of waste management of photovoltaic panels in Ukraine. One of the main tasks for development is to increase the share of waste materials that are currently not disposed of, but can be used as secondary raw materials.